2009
DOI: 10.4049/jimmunol.0900904
|View full text |Cite
|
Sign up to set email alerts
|

Proteases Induce Production of Thymic Stromal Lymphopoietin by Airway Epithelial Cells through Protease-Activated Receptor-2

Abstract: Thymic stromal lymphopoietin (TSLP) is produced by epithelial cells and triggers dendritic cell-mediated Th2-type inflammation. Although TSLP is up-regulated in epithelium of patients with asthma, the factors that control TSLP production have not been studied extensively. Because mouse models suggest roles for protease(s) in Th2-type immune responses, we hypothesized that proteases from airborne allergens may induce TSLP production in a human airway epithelial cell line, BEAS-2B. TSLP mRNA and protein were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
262
3
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(285 citation statements)
references
References 58 publications
(72 reference statements)
5
262
3
12
Order By: Relevance
“…Recent studies indicated important roles of epithelium-derived cytokines, such as IL-33, thymic stromal lymphopoietin, and IL-25, in Th2 responses (50)(51)(52). Papain stimulates the release of thymic stromal lymphopoietin in a human bronchial epithelial cell line (12), and papain and Der p 1 can induce upregulation of IL-25 mRNA expression in a mouse lung epithelial cell line (13). Molecular mechanisms of sensing protease allergens (mediators, sensors, and signaling molecules) to induce the release of these cytokines toward the in vivo responses have yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicated important roles of epithelium-derived cytokines, such as IL-33, thymic stromal lymphopoietin, and IL-25, in Th2 responses (50)(51)(52). Papain stimulates the release of thymic stromal lymphopoietin in a human bronchial epithelial cell line (12), and papain and Der p 1 can induce upregulation of IL-25 mRNA expression in a mouse lung epithelial cell line (13). Molecular mechanisms of sensing protease allergens (mediators, sensors, and signaling molecules) to induce the release of these cytokines toward the in vivo responses have yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Protease activity of house dust mite (HDM) major group 1 allergens (Der f 1 and Der p 1), two of the most important allergens common worldwide, has been shown to cause barrier dysfunction, to induce the production of proinflammatory cytokines in epithelial cells and keratinocytes, to cleave various molecules, to modulate functions of various cell types, and to induce Th2 responses (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Papain, a papaya fruit-derived occupational protease allergen, stimulates epithelial cells (12,13) and mouse basophils in vitro (14,15) and induces Th2 responses (14)(15)(16)(17) and IL-33-dependent innate responses of lung eosinophilia in mice (18). HDM-derived Der f 1 and Der p 1 and plantderived papain belong to the same family of cysteine proteases, family C1 of clan CA (19,20).…”
mentioning
confidence: 99%
“…TLRs may not be associated with the production of TSLP. 8 Our preliminary experiments with nasal polyp fibroblasts showed that when the cells were stimulated with fungi, Alternaria and Aspergillus enhanced the production of IL-6 and IL-8, but not GM-CSF, and maximal cytokine production was found at the 50 μg/mL treatment of both fungi (data not shown). Therefore, we chose 50 and 25 μg/mL of Alternaria and Aspergillus, respectively, for this study.…”
Section: Discussionmentioning
confidence: 92%
“…[97][98][99] Interestingly, allergen extracts and helminths excretory/secretory products often share similar properties that can lead to Type 2-associated responses. For example, both are rich in proteases 100 that can promote Th2 differentiation through protease-activated receptor 2 101-103 directly on T cells 102 or indirectly by inducing IL-33 or thymic stromal lymphopoietin production by tissue cells 104,105 or IL-13 production by macrophages. 106 In addition, both allergens and helminths are known to increase numbers and activity of type extract; AsE = Anisakis simplex extract; CR = cockroach; HDM = house dust mite.…”
Section: -89mentioning
confidence: 99%